2019
DOI: 10.3389/fphys.2019.00330
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Rodent Insula in Anxiety

Abstract: The human insula has been consistently reported to be overactivated in all anxiety disorders, activation which has been suggested to be proportional to the level of anxiety and shown to decrease with effective anxiolytic treatment. Nonetheless, studies evaluating the direct role of the insula in anxiety are lacking. Here, we set out to investigate the role of the rodent insula in anxiety by either inactivating different insular regions via microinjections of glutamatergic AMPA receptor antagonist CNQX or activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 78 publications
5
35
0
Order By: Relevance
“…Our main finding is that post-training inactivation of the pIC, but not the aIC, selectively impaired conditioned freezing response to tone, suggesting that functional inactivation of the pIC during the consolidation time-window is sufficient to severely impair cued but not background contextual fear memories. These results are consistent with the growing evidence that the pIC plays an important role in emotional processing (Gogolla, 2017;Méndez-Ruette et al, 2019), and point to an important role of this insular area not only in integrating exteroceptive and interoceptive signals (Gehrlach et al, 2019;Livneh et al, 2020), but also in consolidating the association between neutral cues and an aversive exteroceptive stimulus. In addition, our results highlight the different functional profiles of aIC and pIC in fear memory consolidation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our main finding is that post-training inactivation of the pIC, but not the aIC, selectively impaired conditioned freezing response to tone, suggesting that functional inactivation of the pIC during the consolidation time-window is sufficient to severely impair cued but not background contextual fear memories. These results are consistent with the growing evidence that the pIC plays an important role in emotional processing (Gogolla, 2017;Méndez-Ruette et al, 2019), and point to an important role of this insular area not only in integrating exteroceptive and interoceptive signals (Gehrlach et al, 2019;Livneh et al, 2020), but also in consolidating the association between neutral cues and an aversive exteroceptive stimulus. In addition, our results highlight the different functional profiles of aIC and pIC in fear memory consolidation.…”
Section: Discussionsupporting
confidence: 90%
“…The insula (or insular cortex, IC) has been implicated in a myriad of functions such as emotion regulation, cognition, interoception, homeostasis and salience processing (Allen, 2020;Benarroch, 2019;Gogolla, 2017;Nieuwenhuys, 2012;Uddin, 2015;Uddin et al, 2014Uddin et al, , 2017. Animal studies have further revealed a key role for the IC in aversive states (Gehrlach et al, 2019;Méndez-Ruette et al, 2019), multimodal processing and integration of visceral and somatosensory inputs (Livneh et al, 2017(Livneh et al, , 2020Rodgers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding anxiety-related behaviors, pharmacological activation of those two insular subregions in rats, respectively induced anxiogenic and anxiolytic effects in the elevated plus maze [21]. However, another recent optogenetic study has reported that close-loop inhibition of glutamatergic neurons of the posterior insula increased exploration of the open arms in the elevated plus maze [22].…”
Section: The Insular Cortex In Anxietymentioning
confidence: 99%
“…The distribution of cells expressing 5-HT1A or/and 5-HT2A transcripts has been analyzed in several subregions of the PFC, and the proportion of 5-HT2A+ glutamatergic cells ranges from 12% (infralimbic area) to 81% (tenia tecta of the olfactory cortex) [34]. In the insular cortex, the functional division of the anterior and posterior insula is well defined in emotional processing, as revealed by 15 opposing optogenetically-induced valence-related behaviors [20,22,29], as well as opposing pharmacologically-induced anxiety-related behaviors [21]. This different role of the anterior and posterior insula led us to analyze the percentage of 5-HT1A+ or 5-HT2A+ cells in the anterior and posterior insula, separately.…”
Section: Difference In Expression Of 5-ht Receptors In the Anterior Amentioning
confidence: 99%